Analisis Faktor-Faktor yang Memengaruhi Tabungan di Indonesia - Sri Astuty; Diah Retno Dwi Hastuti; Citra Ayni Kamaruddin; Muhammad Ilyas Thamrin Tahir (Journal of Economic Education and Entrepreneurship Studies, 2022)
This study aims to analyze the effect of people's income, interest rates and inflation on savings in Indonesia. The independent variables in this study are people's income, interest rates and inflation, while the dependent variable is the amount of savings. The population in this study is data on public income, interest rates and inflation, while 15 samples were used, namely from 2005 to 2019. The research data was obtained from publications from the Central Bureau of Statistics (BPS) and Bank Indonesia. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis conducted in this study, it can be concluded that: (1) people's income has a positive effect on saving in Indonesia; (2) interest rates and inflation have no effect on savings in Indonesia.